Microcirculation After Trochanteric Femur Fractures: A Prospective Cohort Study Using Non-invasive Laser-Doppler Spectrophotometry - Ganse, Bergita; Böhle, Franziska; Pastor, Tatjana; Gueorguiev, Boyko; Altgassen, Simon; Gradl, Gertraud; Kim, Bong-Sung; Modabber, Ali; Nebelung, Sven; Hildebrand, Frank; Knobe, Matthias (Frontiers in Physiology, 2019)
Proximal femur fractures represent a major healthcare problem in the ageing society. High rates of postoperative infections are linked to risk factors that seem to affect local microcirculation. Patterns and time courses of alterations in microcirculation have, however, not been previously investigated. The aim of this prospective cohort study was to evaluate perioperative changes in microcirculation after trochanteric femur fractures using non-invasive laser-Doppler spectrophotometry to analyze how oxygen saturation (SO2), hemoglobin content (Hb) and blood flow changed before and after surgery, and how these parameters were altered by implant type, gender, smoking, diabetes and age. Measurements were separately recorded for nine locations around the greater trochanter in 2mm, 8mm and 15mm depths, before surgery and 8h, 24h, 48h, 4d, 7d and 12d after surgery in 48 patients. Three implants were compared: Dynamic Hip Screw, Gamma3 nail and Percutaneous Compression Plate. Surgery resulted in significant differences between the healthy and injured leg in SO2, Hb and flow. Each parameter showed comparable values for both legs prior to surgery. Significantly higher values in SO2 and flow were registered in women compared to men before and after surgery. Smoking caused significant increases in SO2, Hb and flow only in the superficial layer of the skin after surgery. Diabetes decreased blood flow at 2 and 8mm depth and increased SO2 at 8 and 15 mm depth after surgery. Age revealed a significant negative correlation with flow. The ability to increase the flow rate after surgery decreased with age. Comparison of implants indicated the minimally invasive implant PCCP altered microcirculation less than the DHS or the Gamma3 nail. Overall, the proximal femur fracture alone did not alter local skin microcirculation significantly in a way comparable to the effect caused by surgery. In conclusion, microcirculation after proximal femur fractures is highly affected by surgery, gender, smoking, diabetes, age and implant in ways specified in this study.